2020
DOI: 10.3390/ijms21010365
|View full text |Cite
|
Sign up to set email alerts
|

Pistachio Consumption Alleviates Inflammation and Improves Gut Microbiota Composition in Mice Fed a High-Fat Diet

Abstract: High-fat diet (HFD) induces inflammation and microbial dysbiosis, which are components of the metabolic syndrome. Nutritional strategies can be a valid tool to prevent metabolic and inflammatory diseases. The aim of the present study was to evaluate if the chronic intake of pistachio prevents obesity-associated inflammation and dysbiosis in HFD-fed mice. Three groups of male mice (four weeks old; n = 8 per group) were fed for 16 weeks with a standard diet (STD), HFD, or HFD supplemented with pistachios (HFD-P;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 89 publications
8
43
0
Order By: Relevance
“…Whether higher abundance of this species on the one hand indicates increased body fat, but on the other hand enhances responsiveness to energy-reduction warrants follow-up research. Further, Christensenella minuta has been linked with healthy body composition and Turicibacter with reduction in high-fat diet induced inflammation [59,60,69,70]. Our data showing negative correlation of Christensenella and Turicibacter with body-fat while undergoing weight-loss support these prior observations.…”
Section: Discussionsupporting
confidence: 84%
“…Whether higher abundance of this species on the one hand indicates increased body fat, but on the other hand enhances responsiveness to energy-reduction warrants follow-up research. Further, Christensenella minuta has been linked with healthy body composition and Turicibacter with reduction in high-fat diet induced inflammation [59,60,69,70]. Our data showing negative correlation of Christensenella and Turicibacter with body-fat while undergoing weight-loss support these prior observations.…”
Section: Discussionsupporting
confidence: 84%
“…In previous studies, the colitis induced by TNBS (2,4,6-Trinitrobenzenesulfonic acid) or oxazolone model had revealed improvement in sulfate-reducing bacteria colonization, and Desulfovibrio could exacerbate the alterations with activation of the immune response and colitis development [ 42 ]. Also, high-fat diet-induced gut dysbiosis could modulate the abundance of Oscillospira , Desulfovibrio , Coprobacillus , and Bilophila associated with inflammation [ 43 ]. Another study has also demonstrated that oligosaccharides could ameliorate inflammation and its complications in high-fat diet-induced obesity by decreasing the abundances of the Desulfovibrio , Anaerotruncus , Mucispirillum , Roseburia , and Odoribacter [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with chronic low-grade inflammation which eventually leads to abnormal metabolisms. A recent study conducted on mice demonstrated that chronic intake of pistachio exerts beneficial effects in obese mice by alleviating inflammation in adipose tissues and liver, and impacting the gut microbiome composition [94]. Nuts are very energy dense food item and there are reports of weight gain with increased consumption of nuts without energy balance.…”
Section: Pistachio and Obesitymentioning
confidence: 99%